BEHAVIOR OF A STEEL STRUCTURE RAILWAY BRIDGE UNDER DYNAMIC LOADINGS - Nadi, Muhammad Abi Berkah; Aspar, Wimpie Agoeng Noegroho; Barasa, Willy; Primadiyanti, Suci Putri; Aritenang, Wendy; Karunia, Meutia Nadia; Halawa, Boy Jurdil (Journal of Applied Engineering Science, 2024)
Most old steel structure railway bridges in Indonesia have deteriorated throughout their service life since they were constructed almost a century ago. However, those bridges’ performance must be maintained to have essential safety issues and live extension of the railway bridge structure. Therefore, inspecting and evaluating those steel railway bridges is necessary to maintain the service requirement. Vertical deformation of the steel railway bridge caused by dynamic loadings needs to be observed. The objective of the study is to assess the old steel railway bridge by evaluating the strength characteristics of the structures against the working forces, particularly the moving, wind, and seismic loads. In order to understand the phenomena impacted by the dynamic loadings, the steel structure railway bridge was instrumented using deformation sensors, strain gages, accelerometers, and passive infrared. The steel railway bridge was analyzed using a 3D finite element model. This study discussed the influence of dynamic loadings on the steel structure railway bridge. This paper elaborates and provides suggestions to solve problems and recommended action in practice for future study. This paper may be useful for researchers and practicing engineers.